Portulaca oleracea polysaccharides reduce serum lipid levels in aging rats by modulating intestinal microbiota and metabolites - Fu, Qiang; Huang, Hui; Ding, Aiwen; Yu, Ziqi; Huang, Yuping; Fu, Guiping; Huang, Yushan; Huang, Xiaoliu (Frontiers in Nutrition, 2022)
Metabolic diseases characterized by dyslipidemia are common health problems for elderly populations. Dietary fiber intake is inversely associated with the risk of dyslipidemia. This study investigated the effects of Portulaca oleracea polysaccharide (POP) on the intestinal microbiota and its metabolites in aging rats using 16S rRNA sequencing and metabolomics techniques. Our results showed that POPs reduced the ratio of Firmicutes/Bacteroidetes (F/B), relative abundance of Fusobacteria, and levels of triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), alanine aminotransferase (ALT), and gamma-glutamyl transferase (γ-GT) in the serum of aging rats. POP supplementation also reduced 5beta-cholestane-3alpha,7alpha,12alpha,25-tetrol, and vaccenic acid concentrations in lipids and lipoid-like molecules, while soyasapogenol E and monoacylglycerol (MG) (24:0/0:0/0:0) levels increased. This study demonstrated that POP’s beneficial effects on lipid levels in aging rats might be partially attributable to the modification of gut microbiota and related metabolites.